2006
DOI: 10.1348/000709905x49890
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and depression in early–mid adolescence: A longitudinal study

Abstract: Current policy focuses on victimization as a cause of distress; however, professionals should be aware that vulnerable children and young people are likely to be the targets of victimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
156
2
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(185 citation statements)
references
References 65 publications
12
156
2
15
Order By: Relevance
“…Other studies have shown that children with internalising and externalising problems are more likely to later become victims of bullying [8,22]. Hodges and Perry [22] and Sweeting et al [56] particularly concluded that associations between bullying and internalising and social problems were reciprocal. This was also suggested by Sourander et al [53] in a follow-up from childhood to adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that children with internalising and externalising problems are more likely to later become victims of bullying [8,22]. Hodges and Perry [22] and Sweeting et al [56] particularly concluded that associations between bullying and internalising and social problems were reciprocal. This was also suggested by Sourander et al [53] in a follow-up from childhood to adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, internalizing problems may not just be the consequences but also, although weak, the antecedents of victimization (r=.08) -a reciprocal influence, which may lead to a vicious circle (Kaltiala-Heino et al 2010;Sweeting et al 2006). This further illustrates the importance of controlling for internalizing symptoms which predate the onset of victimization in study designs.…”
mentioning
confidence: 99%
“…Victimization in adolescence significantly predicts depression symptoms in both the short term (1-4 years later) (Bond et al 2001;KaltialaHeino et al 2010;Sweeting et al 2006) and long term (Klomek et al 2008). For example, Klomek and colleagues (2008) showed that those who were bully-victims (children who were both bullies and victims) at the age of 8 years had 4 times increased odds of severe depression scores 10 years later.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have described associations between bullying by peers and a number of different dimensions of internal distress and social problems. Students affected by bullying will be at higher risk of developing depression, anxiety, loneliness, mistrust of others, low self-esteem, poor social adjustment, poor academic achievement, and poor health as compared to others (Aluede, Adeleke, Omoike, & Afen-Akpaida, 2008;Beran, 2009;Cassidy, 2009;ConnersBurrow, Johnson, Whiteside-Mansell, McKelvey, & Gargus, 2009;DeRosier & Mercer, 2009;Fleming & Jacobsen, 2009;Hawker & Boulton, 2000;Prinstein, Boergers, & Vernberg, 2001;Ranta, Kaltiala-Heino, Pelkonen, & Marttunen, 2009;Rigby, 2003;Roland, 2002;Sweeting, Young, West, & Der, 2006;Thijs & Verkuyten, 2008).…”
mentioning
confidence: 99%